Measuring radon flux across active faults : relevance of excavating and possibility of satellite discharges - Richon, Patrick (2014)
Searching for gas exhalation around major tectonic contacts raises important methodological issues such as the role of the superficial soil and the possible long distance transport. These effects have been studied on the Xidatan segment of the Kunlun Fault, Qinghai Province, China, using measurement of the radon-222 and carbon dioxide exhalation flux. A significant radon flux, reaching up to 538 ± 33 mBq m−2 s−1 was observed in a 2–3 m deep trench excavated across the fault. On the soil surface, the radon flux varied from 7 to 38 mBq m−2 s−1, including on the fault trace, with an average value of 14.1 ± 1.0 mBq m−2 s−1, similar to the world average. The carbon dioxide flux on the soil surface, with an average value of 12.9 ± 3.3 g m−2 day−1, also remained similar to regular background values. It showed no systematic spatial variation up to a distance of 1 km from the fault, and no clear enhancement in the trench. However, a high carbon dioxide flux of 421 ± 130 g m−2 day−1 was observed near subvertical fractured phyllite outcrops on a hill located about 3 km north of the fault, at the boundary of the large-scale pull-apart basin associated with the fault. This high carbon dioxide flux was associated with a high radon flux of 607 ± 35 mBq m−2 s−1. These preliminary results indicate that, at the fault trace, it can be important to measure gas flux at the bottom of a trench to remove superficial soil layers. In addition, gas discharges need to be investigated also at some distance from the main fault, in zones where morphotectonics features support associated secondary fractures.